CESifo World Economic Survey November 2013 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe; Timo Wollmershäuser (CESifo World Economic Survey, 2013)
World Economic Climate: World economic climate brightens - Economic Expectations: Economic expectations clearly more optimistic - Inflation: Inflation expectations unchanged - Currencies: US dollar expected to rise -Interest Rates: Long-term interest rates likely to rise - Special Topic: The multilateral trading system
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies